Pengaruh Kompetensi, Independensi, Skeptisme, dan Pengalaman Kerja Terhadap Kemampuan Auditor Internal dalam Mendeteksi Kecurangan (Fraud) - tamara, elvira; Badera, I Dewa Nyoman (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study aim to determine the effect of competence, independence, skepticism, and work experience on the ability of internal auditors to detect fraud. This research was conducted at Bank Negara Indonesia (BNI) Bali Province with a non-probability sampling method, namely saturated sampling. Data collection was carried out through distributing questionnaires to 36 auditors. The data analysis method used is multiple linear regression analysis. The results showed that competence, independence, skepticism, and work experience have a positive effect on the ability of internal auditors to detect fraud.